Pengaruh Model Pembelajaran Dan Minat Belajar Terhadap Hasil Belajar Statistik - Prasetya, Budi; Muchtar, Hartati; Syahrial, Zulfiati (JTP - Jurnal Teknologi Pendidikan, 2018)
The purpose of this research is in order to know the influence of learning model and the interest of study to the result of statictics study. This result be done to the machine engine university student, Study program of machine engine, Jakarta State University. Sample about 120 university students, that be distributed into four clasess. After be done the measurement to the interest of statistics study to each sample by distributing the questioner the intertest of study in the beginning, after that its result be sequenced from the most biggest to the smallest, in order to be taken the upper limite about 27% and the lower limit about 27%, namely 32 university students in each class. Finally, be gotten Finally be gotten final sample about 64 university students from two clasess base on the measurement of study interest.This research be done by the action of eight times of study in each class by using website learning model and directly beended by by given the test of study result for university student in order to know the differentiation after be given the action. The analysis of the research results using two way ANOVA followed by Tukey test. The result of the research shows that: (1) the learning result of the students who are learn by the learning model of the website is higher than the result of student learning learn by direct learning model, (2) there is interaction between the learning model of the website with the interest of learning toward the student’s learning result, (3) The learning outcomes of students who have high interest and are learn with the learning model of the website are higher than the results of student learning learn by direct learning model, and (4) the learning outcomes of students who have low interest and learn by direct learning model is not higher than student learning outcomes which is learn by website learning model